1991
DOI: 10.1007/bf01625429
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions between differentiation-inducing agents in inhibiting the proliferation of HL-60 human myeloid leukaemia cells in clonogenic micro assays

Abstract: All-trans-retinoic acid, hexamethylene bisacetamide and 5-azacytidine are inducers of granulocytic differentiation of HL-60 human myeloid leukaemic cells, which eventually leads to inhibition of cell proliferation. The effect of graded concentrations of all-trans-retinoic acid (RA) (1 nM-1 microM), hexamethylene bisacetamide (HMBA) (0.5-4 mM) and/or 5-azacytidine (5azaC) (1 nM-1 mM), alone and in combination with each other on colony formation and growth of HL-60 cells was studied in agar capillary clonogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…6,7 Also, HMBA is usually used to cooperate with other antitumor drugs to get a better effect on differentiation. 8,9 However, so far the induced differentiation mechanism of HMBA is not demonstrated clearly. On the other hand, glucose and sucrose are important biological substances in the bodies of animals and plants, and hence the drug getting into living body most probably interacts with the sugars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Also, HMBA is usually used to cooperate with other antitumor drugs to get a better effect on differentiation. 8,9 However, so far the induced differentiation mechanism of HMBA is not demonstrated clearly. On the other hand, glucose and sucrose are important biological substances in the bodies of animals and plants, and hence the drug getting into living body most probably interacts with the sugars.…”
Section: Introductionmentioning
confidence: 99%
“…To humans, cancer is the second killer in all types of diseases. Research on various cancers and antitumor drugs has been ongoing for years. Among various antitumor drugs, N , N ′-hexamethylenebisacetamide (HMBA), a small polar molecule compound, cannot only induce differentiation of leukemia cells but also could lead to a variety of tumor cells to normal differentiation. , At the present, people have done a series of research on the function of HMBA to Burkitt lymphoma Raji cells, malignant pleural mesothelioma, and so forth. , Also, HMBA is usually used to cooperate with other antitumor drugs to get a better effect on differentiation. , However, so far the induced differentiation mechanism of HMBA is not demonstrated clearly. On the other hand, glucose and sucrose are important biological substances in the bodies of animals and plants, and hence the drug getting into living body most probably interacts with the sugars.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the level of differentiation of 5-Aza-induced THP-1 cells was determined by microscopy and by assessing the expression levels of CD14. The results indicated that 5-Aza produces a similar biological effect on cell differentiation in THP-1 cells to different types of AML cell lines (12,20). 5-Aza is hypothesized to induce differentiation by inhibiting DNA methylation and upregulating the expression of transcription factors associated with differentiation.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have reported that 5-Aza exerts a number of effects in different leukemia cell lines, including inhibition of cell proliferation and induction of differentiation (6,12). THP-1, a monocytic leukemia cell line driven by the MLL-AF9 fusion gene, was employed for the purposes of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation